2022
DOI: 10.1177/21582440221127190
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance Behavior Among Malaysian Taxpayers: A Dual-stage PLS-SEM and ANN Analysis

Abstract: The tax system provides the necessary financial resources to a country’s administration to use the collected resources for the welfare of the general public and the development of general infrastructure. Therefore, compliance with the prevailing tax system is necessary for a country’s political and administrative system to survive. The current study aims to explore the intention to comply and the compliance behavior toward the tax system among Malaysian taxpayers. The data were collected using the survey metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
2
7
3
Order By: Relevance
“…In addition, an individual's decision to comply with tax rules and regulations may be influenced by their perception of the level of control they have over the behaviour. Nevertheless, the finding was in contrast to Hayat et al (2022) who found that taxpayers in Malaysia did not comply with tax regulations due to a lack of perceived civic duty and discomfort with paying taxes on time and in full.…”
Section: Results and Analysiscontrasting
confidence: 97%
See 1 more Smart Citation
“…In addition, an individual's decision to comply with tax rules and regulations may be influenced by their perception of the level of control they have over the behaviour. Nevertheless, the finding was in contrast to Hayat et al (2022) who found that taxpayers in Malaysia did not comply with tax regulations due to a lack of perceived civic duty and discomfort with paying taxes on time and in full.…”
Section: Results and Analysiscontrasting
confidence: 97%
“…Imposing higher penalties is an effective way to discourage noncompliant attitudes towards taxes (Mohdali et al, 2014). Tax penalties can serve as a deterrent to encourage taxpayers to comply with the tax system (Hayat et al, 2022). However, previous research has demonstrated that legal enforcement techniques, such as tax fines, may not ensure tax law compliance (Murphy, 2008).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Neither direct ( β = 0.005, p > 0.1) nor indirect effects ( β = 0.006, p > 0.1) were found to be insignificant, while the size of the effects was found to be very small. These findings did not support previous studies (Kaulu, 2022; Youde and Lim, 2019; Hayat et al. , 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, their level of compliance is influenced by their impression of whether those with similar incomes are exposed to the same tax burden. This confirms what other research has shown across various contexts (Hayat et al. , 2022; Inasius, 2019a; Jimenez and Iyer, 2016; Lois et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation